Gill arch and raker morphology of common carp (Cyprinus carpio, Linnaeus, 1758) sampled in aquaculture system - Demirci, Beste; Kesbiç, Osman Sabri (Wiley, 2023)
AbstractThe study aimed to investigate the morphologic aspects of common carp's gill arch and gill rakers (Cyprinus carpio, Linnaeus, 1758), an omnivore and highest‐produced aquaculture species. The study used 10 common carp (395.35 ± 45.06 g) grown entirely under aquaculture conditions. The fish tissues were fixed with Glutaraldehyde (2.5%) for scanning electron microscopy and with formalin (10%) for stereomicroscopic examination. In the SEM examination, two types of taste papillae (Type II and Type III) were observed in the pharyngeal mucosa. Microridge‐like structures in the epithelial layer were found to have two forms. The study findings indicate a significant decrease in gill arch lengths from cranial to caudal and a significant increase in rakers per unit area, as determined through digital calliper measurements and stereomicroscopic examinations (p < 0.05). However, there was no significant difference in measurements of gill arches and raker numbers between the bilateral symmetry of the gill arches (p > 0.05). In conclusion, it was observed that the epithelial structure on the common carp gill arch contained two types of microridge‐like structures: the gill arch length decreased from cranial to caudal, and the rake density on these arches increased caudally.
Keywords: Gills; Carps; Mucous Membrane; Microscopy, Electron, Scanning; Animals; Pharynx; Aquaculture; 14. Life underwater